Immunologic Consequences of Hypoxia during Critical Illness. (July 2016) - Kiers, Harmke D.; Scheffer, Gert-Jan; van der Hoeven, Johannes G.; Eltzschig, Holger K.; Pickkers, Peter; Kox, Matthijs
Abstract : Hypoxia and immunity are highly intertwined at clinical, cellular, and molecular levels. The prevention of tissue hypoxia and modulation of systemic inflammation are cornerstones of daily practice in the intensive care unit. Potentially, immunologic effects of hypoxia may contribute to outcome and represent possible therapeutic targets. Hypoxia and activation of downstream signaling pathways result in enhanced innate immune responses, aimed to augment pathogen clearance. On the other hand, hypoxia also exerts antiinflammatory and tissue-protective effects in lymphocytes and other tissues. Although human data on the net immunologic effects of hypoxia and pharmacologic modulation of downstream pathways are limited, preclinical data support the concept of tailoring the immune response through modulation of the oxygen status or pharmacologic modulation of hypoxia-signaling pathways in critically ill patients. Abstract : Hypoxia affects molecular and cellular inflammatory processes and may thereby affect outcome in critical illness. Modulating oxygenation and pharmacologic interventions in hypoxia-singling pathways could support immunologic functions in these patients.